Diagnostic challenges within the Bacillus cereus-group: finding the beast without teeth. (November 2022) - Muigg, Veronika; Cuénod, Aline; Purushothaman, Srinithi; Siegemund, Martin; Wittwer, Matthias; Pflüger, Valentin; Schmidt, Kristina M.; Weisser, Maja; Ritz, Nicole; Widmer, Andreas; Goldenberger, Daniel; Hinic, Vladimira; et al.
Abstract: The Bacillus cereus -group ( B. cereus sensu lato ) includes common, usually avirulent species, often considered contaminants of patient samples in routine microbiological diagnostics, as well as the highly virulent B. anthracis . Here we describe 16 isolates from 15 patients, identified as B. cereus -group using a MALDI-TOF MS standard database. Whole genome sequencing (WGS) analysis identified five of the isolates as B. anthracis species not carrying the typical virulence plasmids pXO1 and pXO2, four isolates as B. paranthracis, three as B. cereus sensu stricto, two as B. thuringiensis, one as B. mobilis, and one isolate represents a previously undefined species of Bacillus ( B. basilensis sp. nov.). More detailed analysis using alternative MALDI-TOF MS databases, biochemical phenotyping, and diagnostic PCRs, gave further conflicting species results. These cases highlight the difficulties in identifying avirulent B. anthracis within the B. cereus -group using standard methods. WGS and alternative MALDI-TOF MS databases offer more accurate species identification, but so far are not routinely applied. We discuss the diagnostic resolution and discrepancies of various identification methods.